Contribution of Learning Interest, Self-Efficacy, Peer Support and Learning Motivation to Students' Learning Independence - Furqon, Wida Mazyda Al-Labibah; Ramli, M; Atmoko, Adi (Buletin Konseling Inovatif, 2025)
This research aims to determine the contribution of learning interest, self-efficacy, peer support, and learning motivation to students’ learning independence. Employing a correlational research design, the study involved 100 students from two different junior high schools located in Malang, Indonesia. Data were collected through a structured questionnaire designed to measure each of the variables. The analysis revealed that each of the factors learning interest, self-efficacy, peer support, and learning motivation significantly contributes to students' learning independence. Furthermore, the collective influence of these factors underscores the importance of fostering a supportive learning environment that enhances student engagement, confidence, and motivation. These findings suggest that educational strategies aimed at increasing interest, bolstering self-efficacy, encouraging peer support, and motivating students can effectively promote greater learning independence, ultimately leading to improved educational outcomes. This study adds to the growing body of literature on the factors influencing student independence and provides practical insights for educators and policymakers.